Sensitivity Analysis for Modeling of Cr(VI) Transfer From Soil to Surface Runoff - Wu, Xiujie; Xu, Zhongyuan; Tong, Juxiu; Hu, Bill X. (Frontiers in Environmental Science, 2022)
Heavy metal contamination in soil has become a serious environmental problem in China, and chromium is one of the major threats to human health. In order to better understand the transfer pattern of heavy metal hexavalent chromium from polluted sites into surface water, the influencing factors that affect solute transfer from soil into the surface runoff with linear and nonlinear adsorption equations based on a two-layer incomplete mixing model were analyzed in this study. The Quasi-Newton method was used to optimize model parameters by fitting with the experimental laboratory data of chromium (Cr(VI)) in surface runoff. The local sensitivity analysis and the Morris global sensitivity analysis approaches were used to assess the parameter importance of rainfall intensity p, the thickness of the mixing layer hmix, incomplete mixing parameter α and γ, the soil adsorption parameters, and the initial soil water content θ0. The study results showed that the optimized nonlinear models were better consistent with the experimental results than the linear adsorption equation model. The results of global sensitivity indicated that rainfall intensity p was the main factor influencing Cr(VI) transport from the soil into surface runoff. The hmix and the α in the two-layer model were vital parameters that influenced such transport processes. Moreover, the soil adsorption properties and the θ0 had the lowest effects on runoff Cr(VI) loss. The results indicate that for controlling pollution migration in surface runoff, it is essential to focus on the analysis of precipitation conditions and soil properties that control the thickness of the mixing layer and the degree of mixing.